Positive electrode active material and lithium secondary battery including same
By using bimodal positive electrode active substances in lithium secondary batteries, including nickel-based lithium composite oxides and cobalt-free lithium composite oxides of different particle sizes and compositions, the problem of decreasing electrochemical performance and stability in the prior art is solved, and higher electrochemical performance, stability and cost reduction are achieved.
Patent Information
- Application Number
- CN202411399696.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-10
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-11
AI Technical Summary
In the case where the positive electrode active substance of the existing lithium secondary battery is reduced, the electrochemical performance and stability are difficult to maintain, resulting in deterioration of the performance of the lithium secondary battery.
A bimodal positive electrode active material is used, which contains a first lithium composite oxide and a second lithium composite oxide having different particle sizes and compositions. Electrochemical performance and stability are improved by presenting the nickel-based lithium composite oxide and the cobalt-free lithium composite oxide in a bimodal form.
The bimodal cathode active substance can improve the electrochemical performance and stability of lithium secondary batteries, reduce the cobalt content, and thus reduce the cost of the cathode active substance.
Smart Images

Figure CN119812303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more particularly to a bimodal positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having different particle sizes and compositions and a lithium secondary battery including the same. Background Art
[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.
[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Lithium composite oxides are used as positive electrode active materials for lithium secondary batteries. For example, LiCoO 2 、LiMN 2 O 4 、LiNiO 2 、LiMnO 2 etc. composite oxides.
[0005] Among the above positive electrode active materials, LiCoO 2 It is the most widely used due to its excellent life performance and charge and discharge efficiency, but has the disadvantage of limited price competitiveness due to the high price of cobalt used as a raw material.
[0006] LiMnO 2 、LiMN 2 O 4 Lithium manganese-based oxides such as LiNiO have the advantages of excellent thermal stability and low price, but have the problems of small capacity and poor high temperature characteristics. 2 The cathode active material exhibits battery characteristics of high discharge capacity, but is difficult to synthesize due to active cation mixing between lithium and nickel, and also has problems of low rate performance and life performance of the synthesized cathode active material.
[0007] Therefore, in order to maintain the LiNiO 2In order to improve the low rate performance and life performance while improving the high reversible capacity, the so-called ternary type, the so-called NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) ternary type or NCMA (Ni-Co-Mn-Al) quaternary type lithium composite oxides in which part of nickel is replaced by cobalt, manganese and / or aluminum have been developed. Since the lower the nickel content in the ternary or quaternary lithium composite oxide as described above, the lower the reversible capacity, therefore, recently, active research has been conducted to increase the nickel content in the lithium composite oxide.
[0008] Commercially available ternary or quaternary lithium composite oxides include cobalt as an essential element in order to achieve a balance between electrochemical performance and particle stability, which have a trade-off relationship.
[0009] However, in recent years, with the rapid growth of demand for lithium secondary batteries, the cost of raw materials has also increased, and the lithium secondary battery market is facing a strong demand for cost reduction. In particular, positive electrode active materials account for the largest share of the cost of lithium secondary batteries, among which cobalt, an essential element of ternary or quaternary lithium composite oxides, is not only the most expensive metal, but also unstable in supply and demand. Therefore, the market demand for positive electrode active materials that reduce costs by adopting low-cobalt or cobalt-free compositions is increasing.
[0010] However, as described above, in commercially available ternary or quaternary lithium composite oxides, cobalt is an essential element required to achieve both electrochemical performance and particle stability.
[0011] For example, it is reported that as the cobalt content in a ternary or quaternary lithium composite oxide decreases, microcracks are formed within the particles due to volume shrinkage / expansion of the lithium composite oxide (e.g., stress-causing anisotropic change) during charge / discharge. As more microcracks are formed within the particles, the electrolyte penetrates into the particles along the microcracks, accelerating particle decomposition, and this phenomenon can lead to performance degradation of lithium secondary batteries.
[0012] In addition, as the cobalt content in the ternary or quaternary lithium composite oxide decreases, the resistance of the positive electrode active material increases and the rate performance deteriorates. Therefore, even if a low cobalt (generally a cobalt content of less than 10 mol%) or cobalt-free composition is used, it is necessary to develop a positive electrode active material to maintain the electrochemical performance of the positive electrode active material at a level similar to that of commercialized positive electrode active materials. Summary of the invention
[0013] Technical issues
[0014] In the lithium secondary battery market, while the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, the demand for positive electrode active materials used in lithium secondary batteries is also changing.
[0015] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, but recently, the use of nickel-based lithium composite oxides having a larger energy capacity per unit weight than LFP is expanding (of course, relatively cheap LFP is still used at present to reduce costs).
[0016] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries recently, generally have ternary types such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or quaternary types such as NCMA (Ni-Co-Mn-Al). However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, the development of positive electrode active materials with low cobalt or cobalt-free compositions is required.
[0017] In recent years, some companies have launched positive electrode active materials with low cobalt or cobalt-free composition, but the overall evaluation shows that their electrochemical performance or stability is not yet sufficient to replace the existing commercial positive electrode active materials.
[0018] For example, as the cobalt content in a ternary or quaternary lithium composite oxide decreases, the resistance of the positive electrode active material increases, resulting in an inevitable decrease in the electrochemical performance of the lithium secondary battery, such as the rate capability.
[0019] In addition, as the cobalt content in the ternary or quaternary type lithium composite oxide decreases, the stability of the particles (crystal stability, thermal stability or particle strength, etc.) decreases rapidly, resulting in early degradation of the life of lithium secondary batteries using the above lithium composite oxide as the positive electrode active material.
[0020] Although the electrochemical performance and stability of existing lithium composite oxides with low cobalt or cobalt-free compositions are indeed slightly lower than those of commercially available ternary or quaternary lithium composite oxides, the inventors of the present invention have confirmed that bimodal positive electrode active materials designed to contain cobalt-containing nickel-based lithium composite oxides and cobalt-free lithium composite oxides can exhibit commercially viable electrochemical performance and stability.
[0021] Therefore, the object of the present invention is to provide a bimodal positive electrode active material, which is a bimodal positive electrode active material comprising a first lithium composite oxide and a second lithium composite oxide with different particle sizes and compositions, and by making the nickel-based lithium composite oxide and the cobalt-free lithium composite oxide exist in a bimodal form, thereby having improved electrochemical performance and stability compared with the existing lithium composite oxides with low cobalt or cobalt-free composition.
[0022] In addition, another object of the present invention is to provide a positive electrode comprising the positive electrode active material defined herein.
[0023] In addition, another object of the present invention is to provide a lithium secondary battery using the positive electrode defined herein.
[0024] The purpose of the present invention is not limited to the purpose mentioned above (for example, electric vehicle use), and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.
[0025] Solutions to the problem
[0026] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a bimodal positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having an average particle size larger than that of the first lithium composite oxide.
[0027] In one embodiment, the first lithium composite oxide may include first bulk particles containing at least nickel and cobalt, and the second lithium composite oxide may include second bulk particles free of cobalt.
[0028] In one embodiment, the first block-shaped particles may be represented by the following Chemical Formula 1.
[0029] [Chemical formula 1]
[0030] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2
[0031] Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, M1 and M2 are different from each other, 0.5≤w≤1.5, 0 <x≤0.40,0≤y≤0.30,0≤z≤0.20。
[0032] In one embodiment, the second block-shaped particles may be represented by the following Chemical Formula 2.
[0033] [Chemical formula 2]
[0034] Lia Ni 1-(b+c) M3 b M4 c O 2-α X α
[0035] Among them, M3 is at least one selected from Mn and Al, M4 is at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, M3 and M4 are different elements, X is at least one anionic element selected from F, P, S, Cl, and Br, 0.5 ≤ a ≤ 1.5, 0 ≤ b ≤ 0.50, 0 ≤ c ≤ 0.20, 0 ≤ α ≤ 0.20.
[0036] In some embodiments, in order to improve the electrochemical performance and stability compared with existing lithium composite oxides with low cobalt or cobalt-free compositions, a coating can be formed on the surface of the first massive particles in the above-mentioned bimodal cathode active material.
[0037] Specifically, the coating exists on at least a part of the surface of the first massive particles, and the coating can contain a metal oxide represented by the following Chemical Formula 3.
[0038] [Chemical Formula 3]
[0039] Li d M5 e O f
[0040] Among them, M5 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, 0 ≤ d ≤ 8, 0 < e ≤ 8, 0 < f ≤ 13, and d, e, and f are numbers determined according to the valence of M5 in a stoichiometric ratio.
[0041] In addition, by ensuring that cobalt exists at an appropriate level based on the overall composition of the above-mentioned bimodal cathode active material, the electrochemical performance and stability can be improved compared with existing lithium composite oxides with low cobalt or cobalt-free compositions.
[0042] For this purpose, the coating existing on the surface of the first massive particles can contain a cobalt-containing oxide.
[0043] In other embodiments, in order to improve the electrochemical performance and stability as compared with existing lithium composite oxides having a low cobalt or cobalt-free composition, a coating may be formed on the surface of the second massive particles in the above-described bimodal cathode active material. At this time, the coating may be present on the surfaces of both the first massive particles and the second massive particles of the cathode active material.
[0044] Specifically, the coating is present on at least a part of the surface of the second massive particles, and the coating may include a metal oxide represented by Chemical Formula 4 below.
[0045] [Chemical Formula 4]
[0046] Li g M6 h O i
[0047] Herein, M6 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu; 0 ≤ g ≤ 8, 0 < h ≤ 8, 0 < i ≤ 13; and g, h, and i are numbers determined according to the valence of M6 in a stoichiometric ratio.
[0048] In another embodiment, the coating is present on at least a part of the surface of the second massive particles, and the coating may include a compound represented by LiX' (where X' is an anionic element selected from F, Cl, and Br). For example, the compound represented by LiX' may include LiF. In another embodiment, the coating may include lithium sulfide, lithium sulfate, or lithium phosphate.
[0049] In addition, by ensuring that cobalt is present at an appropriate level based on the overall composition of the above-described bimodal cathode active material, the electrochemical performance and stability can be improved as compared with existing lithium composite oxides having a low cobalt or cobalt-free composition.
[0050] To this end, the coating present on the surface of the second massive particles may include a cobalt-containing oxide.
[0051] Moreover, according to another aspect of the present invention, there is provided a cathode including the above-described cathode active material.
[0052] In addition, according to another aspect of the present invention, there is provided a lithium secondary battery using the above-described cathode.
[0053] Effects of the Invention
[0054] According to the present invention, by providing a bimodal positive electrode active material including a nickel-based lithium composite oxide (first lithium composite oxide) and a cobalt-free lithium composite oxide (second lithium composite oxide) having different particle sizes and compositions, the electrochemical performance and stability can be improved compared to the existing lithium composite oxides with low cobalt or cobalt-free composition.
[0055] In particular, by forming a predetermined coating on the surface of the first bulk particles constituting the first lithium composite oxide and / or the second bulk particles constituting the second lithium composite oxide, it can help improve the electrochemical performance and stability compared with the existing low-cobalt or cobalt-free lithium composite oxides.
[0056] If a coating containing cobalt oxide is formed on the surface of the first block particles constituting the first lithium composite oxide and / or the second block particles constituting the second lithium composite oxide, the cobalt content in the first block particles can be further reduced. As a result, the cobalt content in the overall composition (block composition) of the bimodal positive electrode active material can be reduced, thereby achieving the purpose of reducing the cost of the positive electrode active material.
[0057] In addition, according to the present invention, the electrochemical performance of the positive electrode active material can be further improved by designing the appropriate metal composition of the nickel-based lithium composite oxide (first lithium composite oxide) and the cobalt-free lithium composite oxide (second lithium composite oxide) in the bimodal positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The dQ / dV curve of a lithium secondary battery at the time of initial discharge is shown according to changes in the molar fractions of nickel and manganese in the positive electrode active material (lithium composite oxide).
[0059] Figure 2 The dQ / dV curves of lithium secondary batteries manufactured using the positive electrode active materials according to Examples 1 to 3 at the time of initial discharge are respectively shown.
[0060] Figure 3 The dQ / dV curves of lithium secondary batteries manufactured using the positive electrode active materials according to Comparative Examples 1 to 3 at the time of initial discharge are respectively shown. DETAILED DESCRIPTION
[0061] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.
[0062] Hereinafter, a cathode active material according to the present invention and a lithium secondary battery including the cathode active material will be described in more detail.
[0063] Positive active material
[0064] According to one aspect of the present invention, there is provided a bimodal positive electrode active material including a first lithium composite oxide and a second lithium composite oxide having different particle sizes and compositions.
[0065] In one embodiment, the bimodal positive electrode active material may include a first lithium composite oxide and a second lithium composite oxide having an average particle size greater than that of the first lithium composite oxide. The first lithium composite oxide having a relatively small average particle size may be referred to as a small particle, and the second lithium composite oxide having a relatively large average particle size may be referred to as a large particle.
[0066] The average particle size of the first lithium manganese-based oxide and the second lithium composite oxide in the positive electrode active material can be measured using a laser diffraction method. For example, after the lithium composite oxide (small particles or large particles) is dispersed in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (for example, Microtrac MT 3000), irradiated with an ultrasonic wave of about 28kHz at a power of 60W, and then a volume cumulative particle size distribution chart is obtained. The particle size corresponding to 50% of the volume cumulative amount is determined and defined as the average particle size (D 50 ). In other cases, the average particle size of the first lithium composite oxide and the second lithium composite oxide in the positive electrode active material can be calculated as the average value of the particle sizes of small particles and large particles confirmed by SEM images.
[0067] In the present invention, the average particle size (D 50 ) is not particularly limited in scope.
[0068] For example, small particles can refer to the average particle size (D 50 ) is less than 7 μm, less than 6.5 μm, less than 6 μm, less than 5.5 μm, less than 5 μm, less than 4.5 μm, less than 4 μm, less than 3.5 μm or less than 3 μm. In order to prevent excessive aggregation between the above-mentioned small particles, the average particle size (D 50 ) is preferably 0.5 μm or more, 1 μm or more, 1.5 μm or more, or 2 μm or more. For example, the large particles may refer to the average particle size (D 50) is greater than 7 μm, greater than or equal to 7.5 μm, greater than or equal to 8 μm, greater than or equal to 8.5 μm, greater than or equal to 9 μm, greater than or equal to 9.5 μm, greater than or equal to 10 μm, greater than or equal to 10.5 μm, greater than or equal to 11 μm, greater than or equal to 11.5 μm or greater than or equal to 12 μm. The average particle size (D 50 ) is preferably less than 30 μm, less than 27.5 μm, less than 25 μm, less than 22.5 μm, less than 20 μm, less than 17.5 μm or less than 15 μm, so that small particles with relatively small average particle size are present in the gaps formed by the above-mentioned large particles in a fully filled state.
[0069] In the bimodal positive electrode active material according to various embodiments of the present invention, the first lithium composite oxide and the second lithium composite oxide may be mixed in a weight ratio of 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25 or 80:20. In addition, the first lithium composite oxide and the second lithium composite oxide may be mixed in any weight ratio between 5:95 and 80:20.
[0070] At this time, the first lithium composite oxide may exist in the form of filling the gaps between the second lithium composite oxides, or may be attached to the surface of the second lithium composite oxide, or may exist in the form of agglomeration of the first lithium composite oxides. However, preferably, the first lithium composite oxide having a relatively small average particle size exists in the gaps formed by the plurality of second lithium composite oxides in a state of being fully filled.
[0071] By filling the gaps between large particles with small particles having a relatively small average particle size, the integration density of the lithium composite oxide per unit volume is increased, thereby increasing the energy density per unit volume. In addition, by filling the gaps between large particles with small particles having a relatively small average particle size, the volume change during charge / discharge can be reduced or the stress generated by the volume change can be minimized, thereby preventing the occurrence of microcracks.
[0072] When the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is too small, it may be difficult to fully fill the voids formed by the second lithium composite oxide with the first lithium composite oxide. On the other hand, when the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is too high, the ratio of mutual aggregation of the first lithium composite oxide in the positive electrode active material increases, which may reduce the stability of the positive electrode active material, for example, the compression density of the positive electrode active material decreases.
[0073] In one embodiment, the first lithium composite oxide may include first block particles containing at least nickel and cobalt, and the second lithium composite oxide may include second block particles that are cobalt-free. Block particles refer to single particles or secondary particles. The second block particles being cobalt-free means that the second block particles are substantially free of cobalt. However, in some embodiments, when a coating is present on at least a portion of the surface of the second block particles, the coating may contain cobalt. Therefore, even if a coating containing cobalt is present on at least a portion of the surface of the second block particles, if the second block particles do not contain cobalt, the second block particles may be defined as having a cobalt-free composition. In addition, the second lithium composite oxide may include second block particles that are cobalt-free and contain at least nickel and manganese.
[0074] For example, the particles having the average particle size and composition defined as the first lithium composite oxide and the second lithium composite oxide may be single particles in a non-agglomerated state or secondary particles in the form of agglomerates of a plurality of primary particles. In this case, both the single particles and the secondary particles may be referred to as bulk particles.
[0075] Therefore, the first bulk particles refer to single particles and secondary particles having an average particle size and composition defined as the first lithium composite oxide, and the second bulk particles refer to single particles and secondary particles having an average particle size and composition defined as the second lithium composite oxide.
[0076] As described above, in the case of a bimodal positive electrode active material, small particles with a relatively small average particle size are filled in the gaps between large particles, thereby increasing the integration density of the lithium composite oxide per unit volume, which can increase the energy density per unit volume and reduce the stress caused by volume changes during charging and discharging to prevent the occurrence of microcracks.
[0077] However, since small particles have a relatively larger specific surface area than large particles in the bimodal positive active material, there is a high possibility of side reactions with the electrolyte (e.g., initial irreversible reactions to form a solid electrolyte interphase (SEI)). Due to this side reaction mechanism, the degradation rate of small particles may be faster than that of large particles. In addition, in the case of lithium composite oxides that have the possibility of dissolving manganese at high temperatures, as the specific surface area increases, manganese dissolution may become more active, thereby accelerating the life degradation due to repeated charging and discharging.
[0078] Therefore, the first block particles as small particles have a composition containing at least nickel and cobalt, while the second block particles as large particles have a cobalt-free composition, which is beneficial for improving the electrochemical performance and stability compared to the existing lithium composite oxides with low cobalt or cobalt-free composition and reducing the cobalt content in the overall composition (block composition) of the bimodal positive electrode active material to achieve the purpose of reducing the cost of the positive electrode active material.
[0079] Preferably, the molar fraction of nickel in the first block particles is greater than the molar fraction of nickel in the second block particles, and the molar fraction of manganese in the first block particles is less than the molar fraction of manganese in the second block particles.
[0080] In order to evaluate the electrochemical performance or electrochemical behavior of the positive electrode active material, a dQ / dV chart is generally used, which differentiates the battery capacity after charge / discharge with voltage. For example, when a lithium secondary battery including a positive electrode using any lithium composite oxide containing nickel and manganese as a positive electrode active material and a negative electrode using lithium foil as a negative electrode is charged / discharged at 25°C, a voltage range of 3.0V to 4.4V, and a discharge rate of 0.1C, the voltage (V) and the battery capacity (Q) at the initial discharge are used as the basis, the X-axis is set to the above voltage (V), the Y-axis is set to the above battery capacity (Q), and the differential value (dQ / dV) of the above battery capacity (Q) to the above voltage (V) is plotted, and there is a peak showing the existence of the H2 (hexagonal phase 2) → H3 (hexagonal phase 3) phase transition in the charging region within the voltage range of 4.1V to 4.3V. In general, as the molar fraction of manganese in the lithium composite oxide increases, the voltage band in which the H2→H3 peak is observed moves to a relatively high voltage. For example, when the molar fraction of manganese in the lithium composite oxide is about 10%, the H2→H3 peak is observed at about 4.21V, and when the molar fraction of manganese increases to about 20%, the H2→H3 peak is observed at about 4.26V.
[0081] As described above, in the dQ / dV curve for any positive active material, when the voltage band of the H2→H3 peak is observed to move to the right, it means that the above-mentioned positive active material can exhibit an appropriate capacity at a relatively high voltage. As the voltage band in which the positive active material can exert an appropriate capacity becomes higher, problems such as reduced stability or premature degradation of the positive active material may occur, and problems such as accelerated gas generation due to side reactions may also occur.
[0082] Therefore, according to an embodiment of the present invention, by providing a bimodal positive electrode active material in which the molar fraction of nickel in the first block particles is greater than the molar fraction of nickel in the second block particles, and the molar fraction of manganese in the first block particles is less than the molar fraction of manganese in the second block particles, the voltage band in which the positive electrode active material can exert appropriate capacity can be reduced.
[0083] The first bulk particle is a lithium composite oxide represented by the following Chemical Formula 1 and having a layered crystal structure.
[0084] [Chemical formula 1]
[0085] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2
[0086] Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, M1 and M2 are different from each other, 0.5≤w≤1.5, 0 <x≤0.40,0≤y≤0.30,0≤z≤0.20。
[0087] w, which represents the ratio of lithium to all elements other than lithium in the first block particles, may be 0.5 to 1.5, 0.75 to 1.25, 0.90 to 1.1, or 0.95 to 1.05.
[0088] In one embodiment, the first bulk particle may be a lithium nickel-based composite oxide having a molar fraction of nickel of 60% or more relative to all elements except lithium in the first bulk particle. In this case, in the chemical formula 1, x+y+z is less than 0.40.
[0089] In addition, according to another embodiment, the molar fraction of nickel relative to all elements except lithium in the above-mentioned first blocky particles can be greater than 65% (in this case, x+y+z is less than 0.35), greater than 70% (in this case, x+y+z is less than 0.30), greater than 75% (in this case, x+y+z is less than 0.25), greater than 80% (in this case, x+y+z is less than 0.20), greater than 85% (in this case, x+y+z is less than 0.15) or greater than 90% (in this case, x+y+z is less than 0.10).
[0090] The molar fraction of cobalt relative to all elements except lithium in the above-mentioned first blocky particles can be less than 40% (in this case, x is less than 0.40), less than 35% (in this case, x is less than 0.35), less than 30% (in this case, x is less than 0.30), less than 25% (in this case, x is less than 0.25), less than 20% (in this case, x is less than 0.20), less than 15% (in this case, x is less than 0.15) or less than 10% (in this case, x is less than 0.10).
[0091] When the above-mentioned first block particles contain manganese and / or aluminum, the molar fraction of manganese and / or aluminum relative to all elements except lithium in the above-mentioned first block particles can be less than 30% (in this case, y is less than 0.30), less than 25% (in this case, y is less than 0.25), less than 20% (in this case, y is less than 0.20), less than 15% (in this case, y is less than 0.15), 10% (in this case, y is less than 0.10) or less than 5% (in this case, y is less than 0.05).
[0092] In addition, in order to improve the electrochemical performance of the first block particles, a dopant (M2) may be contained in the first block particles.
[0093] When the first block particles optionally include a dopant, the dopant may include at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, or at least one selected from P, Sr, Ba, B, Ce, Cr, Mo, Na, K, Ti, Zr, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu. The type and combination of the dopant are appropriately selected within the range that the electrochemical performance and stability of the first block particles and the bimodal positive active material including the first block particles and the second block particles are not adversely affected.
[0094] When the above-mentioned first block particles contain dopants, the molar fraction of the dopants relative to all elements other than lithium in the above-mentioned first block particles can be less than 20% (in this case, z is less than 0.20), less than 10% (in this case, z is less than 0.10), less than 5% (in this case, z is less than 0.05), less than 4% (in this case, z is less than 0.04), less than 3% (in this case, z is less than 0.03), less than 2% (in this case, z is less than 0.02), less than 1% (in this case, z is less than 0.01), less than 0.5% (in this case, z is less than 0.005), less than 0.4% (in this case, z is less than 0.004), less than 0.3% (in this case, z is less than 0.003), less than 0.2% (in this case, z is less than 0.002) or less than 0.1% (in this case, z is less than 0.001).
[0095] The upper and lower limits of the contents of nickel, cobalt, M1, and M2 defined in the above Chemical Formula 1 may be appropriately selected within the range satisfying the above definitions.
[0096] The second bulk particles are represented by the following Chemical Formula 2 and are lithium composite oxides having a layered crystal structure.
[0097] [Chemical formula 2]
[0098] Li a Ni 1-(b+c) M3 b M4 c O 2-α X α
[0099] Among them, M3 is at least one selected from Mn and Al, M4 is at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, M3 and M4 are different elements, X is at least one anion element selected from F, P, S, Cl and Br, 0.5≤a≤1.5, 0≤b≤0.50, 0≤c≤0.20, 0≤α≤0.20.
[0100] a, which represents the ratio of lithium to all elements other than lithium in the second block particles, may be 0.5 to 1.5, 0.75 to 1.25, 0.90 to 1.1, or 0.95 to 1.05.
[0101] As shown in the chemical formula 2, at least a portion of the oxygen in the second blocky particle can be substituted by at least one anion element selected from F, P, S, Cl and Br, preferably F. In particular, F has an ionic radius similar to that of oxygen, so F can be more stably present in the crystal structure of the second blocky particle compared to other anion elements. In addition, F can form a strong MF bond by partially replacing the oxygen that forms the M (metal)-O bond, thereby helping to strengthen the crystal structure of the second blocky particle that is deteriorated due to the exclusion of cobalt.
[0102] In one embodiment, the molar fraction of nickel in the metal elements other than lithium in the second block particles (corresponding to “1-(b+c)” in Chemical Formula 2) may be 0.50 to 0.95, 0.60 to 0.90, or 0.70 to 0.80.
[0103] In the above Chemical Formula 2, when M3 is manganese, the molar fraction of manganese in the metal elements other than lithium in the above second blocky particles (corresponding to "b" in Chemical Formula 2) may be 0.05 to 0.50, 0.10 to 0.40, or 0.10 to 0.30. In this case, b+c in Chemical Formula 2 may be 0.50 or less, 0.45 or less, 0.40 or less, 0.35 or less, or 0.30 or less.
[0104] When the molar fraction of nickel in the second blocky particles is less than 0.50, the ratio of the lithium composite oxide having a spinel crystal structure in the second blocky particles may increase. As the ratio of the lithium composite oxide having a spinel crystal structure in the second blocky particles increases, a higher operating voltage is required, and therefore, the capacity performance of the lithium secondary battery using the second blocky particles as the positive electrode active material may deteriorate. In addition, as the nickel content in the second blocky particles decreases, the cation mixing in the lithium composite oxide may increase overall due to the increase in manganese.
[0105] Specifically, the charge of all transition metals constituting the lithium composite oxide is preferably in a trivalent state so as to present a stable charge neutrality state. At this time, when synthesizing a lithium composite oxide with a low cobalt content and a high manganese content, Mn 4+ becomes excessive, so in order to present a charge-neutral state, it replaces Ni 3+ And you 2+ The content will increase. The excess Ni in the synthesis reaction 2+ Similar to Li + The size of cations can therefore occupy the 3a position of Li in the crystal structure of the lithium composite oxide. This phenomenon is called cation mixing.
[0106] On the other hand, when nickel exists in excess in the second bulk particles, the lithium composite oxide exhibits the same 2 Same properties. LiNiO 2 Not only does it have low thermal stability, but when an internal short circuit occurs due to external pressure in the charging state, the lithium composite oxide decomposes itself, or side reactions occur at the interface and surface between the electrolyte and the lithium composite oxide, leading to the rupture and fire of the lithium secondary battery.
[0107] On the other hand, when the molar fraction of manganese in the second massive particles is greater than 0.50, the same problem as when the molar fraction of nickel is less than 0.50 may occur.
[0108] In addition, in order to improve the electrochemical performance of the second bulk particles having a cobalt-free composition, a dopant (M4) may be contained in the second bulk particles.
[0109] When the second block particles optionally include a dopant, the dopant may include at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, or may include Sr, Ba, B, Ce, Cr, Mo, Na, K, Ti, Zr, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu. The type and combination of the dopant are appropriately selected within the range that the electrochemical performance and stability of the second block particles and the bimodal positive active material including the first block particles and the second block particles are not adversely affected.
[0110] When the above-mentioned second massive particles contain a dopant, the molar fraction of the dopant with respect to all elements other than lithium in the above-mentioned second massive particles may be 20% or less (in this case, c is 0.20 or less), 10% or less (in this case, c is 0.10 or less), 5% or less (in this case, c is 0.05 or less), 4% or less (in this case, c is 0.04 or less), 3% or less (in this case, c is 0.03 or less), 2% or less (in this case, c is 0.02 or less), 1% or less (in this case, c is 0.01 or less), 0.5% or less (in this case, c is 0.005 or less), 0.4% or less (in this case, c is 0.004 or less), 0.3% or less (in this case, c is 0.003 or less), 0.2% or less (in this case, c is 0.002 or less), or 0.1% or less (in this case, c is 0.001 or less).
[0111] In some embodiments, in order to improve the electrochemical performance and stability compared with existing lithium composite oxides having a low cobalt or cobalt-free composition, a coating may be formed on the surface of the first massive particles in the above-mentioned bimodal cathode active material. At this time, a coating may optionally be present on the surface of the second massive particles.
[0112] Specifically, the coating is present on at least a part of the surface of the first massive particles, and the coating may contain a metal oxide represented by the following Chemical Formula 3. The metal oxide represented by the following Chemical Formula 3 is an oxide having a composition different from that of the first massive particles.
[0113] [Chemical Formula 3]
[0114] Li d M5 e O f
[0115] Wherein, M5 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, preferably one or two elements. d, e, and f represent numbers determined from the stoichiometric ratio according to the valence of M5. For example, d, e, and f may be appropriately selected from the range of 0 ≤ d ≤ 8, 0 < e ≤ 8, and 0 < f ≤ 13.
[0116] In addition, by ensuring that cobalt is present at an appropriate level based on the overall composition of the above-mentioned bimodal cathode active material, the electrochemical performance and stability can be improved compared with existing lithium composite oxides having a low cobalt or cobalt-free composition.
[0117] For this purpose, the coating present on the surface of the first massive particles may contain a cobalt-containing oxide. The cobalt-containing oxide may be Coe O f and / or Li d Co e O f is represented by
[0118] When a coating containing cobalt oxide is formed on the surface of the first massive particle, the molar fraction of cobalt among the metal elements other than lithium may be 0.15 or less, preferably 0.11 or less, based on the total composition of the first massive particle and the coating.
[0119] In other embodiments, in order to improve the electrochemical performance and stability compared with existing lithium composite oxides having a low-cobalt or cobalt-free composition, a coating may be formed on the surface of the second massive particle in the bimodal cathode active material. At this time, the coating may be present on the surfaces of both the first massive particle and the second massive particle of the cathode active material.
[0120] Specifically, the coating is present on at least a part of the surface of the second massive particle, and the coating may include a metal oxide represented by the following Chemical Formula 4. The metal oxide represented by the following Chemical Formula 4 is an oxide having a composition different from that of the second massive particle.
[0121] [Chemical Formula 4]
[0122] Li g M6 h O i
[0123] Wherein, M6 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd, and Cu, preferably one or two elements. g, h, and i represent numbers determined from the stoichiometric ratio according to the valence of M6. For example, g, h, and i may be appropriately selected from the range of 0 ≤ g ≤ 8, 0 < h ≤ 8, and 0 < i ≤ 13.
[0124] In addition, by ensuring that cobalt is present at an appropriate level based on the total composition of the bimodal cathode active material, the electrochemical performance and stability can be improved compared with existing lithium composite oxides having a low-cobalt or cobalt-free composition.
[0125] For this purpose, the coating present on the surface of the second massive particle may include a cobalt oxide. The cobalt oxide may be represented by Co e O f and / or Li d Co e O f is represented by
[0126] As described above, the second block particles are cobalt-free, which means that the second block particles do not substantially contain cobalt. However, as defined above, even if there is a coating containing cobalt on at least a portion of the surface of the second block particles, the second block particles do not contain cobalt, and thus the second block particles can be cobalt-free lithium composite oxides.
[0127] When a coating containing cobalt oxide is formed on the surface of the second blocky particle, the molar fraction of cobalt in the metal elements other than lithium based on the overall composition of the second blocky particle and the coating can be less than 0.05, less than 0.04, less than 0.03 or less than 0.02.
[0128] In another embodiment, the coating layer is present on at least a portion of the surface of the second bulk particle, and the coating layer may include a compound represented by LiX' (X' is an anion selected from F, Cl and Br). For example, the compound represented by LiX' may include LiF. LiF may be formed by reacting the fluorine-containing polymer with lithium impurities (e.g., LiOH and Li 2 CO 3 ). In another embodiment, the coating may include lithium sulfide, lithium sulfate or lithium phosphate. In the case of lithium phosphate, it may optionally contain a metal element. The metal element may be at least one metal element selected from M3 and M4.
[0129] Based on the overall composition (bulk composition) of the above-mentioned positive electrode active material including the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide, the molar fraction of cobalt in the metal element other than lithium can be 0.005 or more and 0.05 or less, 0.005 or more and 0.045 or less, 0.005 or more and 0.040 or less, 0.005 or more and 0.035 or less, 0.01 or more and 0.045 or less, 0.01 or more and 0.040 or less, 0.01 or more and 0.035 or less. As used herein, the term overall composition (bulk composition) of the positive electrode active material refers to the average composition of the first lithium composite oxide and the second lithium composite oxide constituting the above-mentioned bimodal positive electrode active material.
[0130] When the molar fraction of cobalt is less than 0.005 based on the overall composition of the above-mentioned bimodal positive electrode active material, the particle stability (crystal stability, thermal stability or particle strength, etc.) of the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide is insufficient, and thus the stable electrochemical performance of the lithium secondary battery may be affected. On the other hand, based on the overall composition of the above-mentioned bimodal positive electrode active material, the molar fraction of cobalt being greater than 0.05 means that it does not meet the purpose of the present invention to improve the electrochemical performance and stability compared with the existing low-cobalt or cobalt-free lithium composite oxide and to reduce the cost of the positive electrode active material by reducing the cobalt content in the overall composition (block composition) of the bimodal positive electrode active material.
[0131] In addition, based on the overall composition (bulk composition) of the above-mentioned bimodal positive electrode active material including the above-mentioned first lithium composite oxide and the above-mentioned second lithium composite oxide, the molar fraction of manganese in the metal elements other than lithium is greater than 0.10 and less than 0.40, greater than 0.10 and less than 0.35, greater than 0.10 and less than 0.30, greater than 0.10 and less than 0.25, greater than 0.15 and less than 0.35, greater than 0.15 and less than 0.35, greater than 0.15 and less than 0.30, greater than 0.15 and less than 0.25, greater than 0.17 and less than 0.40, greater than 0.17 and less than 0.35, greater than 0.17 and less than 0.30 or greater than 0.17 and less than 0.25.
[0132] If the molar fraction of manganese is less than 0.10 based on the overall composition of the above-mentioned bimodal positive active material, the capacity performance (especially discharge capacity) and rate performance of the above-mentioned bimodal positive active material may be insufficient. On the other hand, if the molar fraction of manganese is greater than 0.40 based on the overall composition of the above-mentioned bimodal positive active material, there is a risk that the voltage range in which the above-mentioned positive active material can exert an appropriate capacity may be too high.
[0133] When the manganese content is controlled within the above range based on the overall composition (bulk composition) of the bimodal cathode active material including the first lithium composite oxide and the second lithium composite oxide, a lithium secondary battery using the cathode active material exhibits the following dQ / dV behavior.
[0134] Specifically, when a lithium secondary battery using the above-mentioned positive electrode active material as the positive electrode and lithium foil as the negative electrode is charged and discharged under the conditions of 25°C, a voltage range of 3.0V to 4.4V and a discharge rate of 0.1C, based on the voltage (V) and the battery capacity (Q) at the time of initial discharge, the X-axis is set to the above-mentioned voltage (V), the Y-axis is set to the above-mentioned battery capacity (Q), and in a graph plotted with the differential value (dQ / dV) of the above-mentioned battery capacity (Q) to the above-mentioned voltage (V), a peak may exist in the charging region of 4.1V to 4.2V (more specifically, below 4.2V).
[0135] Typically, the peak that appears in the charging region within the voltage range of 4.1V to 4.3V is a peak that shows the H2 (hexagonal phase 2) → H3 (hexagonal phase 3) phase transition. At this time, as the molar fraction of manganese in the lithium composite oxide increases, the voltage band of the H2 → H3 peak is observed to move to a relatively high voltage. For example, referring to the dQ / dV curve of a lithium secondary battery at the initial discharge that varies with the molar fraction of nickel and manganese in the positive electrode active material (lithium composite oxide), Figure 1 (NM99-Ni:Mn=99:1;NM90-Ni:Mn=90:10;NM80-Ni:Mn=80:20;NM70-Ni:Mn=70:30;NM60-Ni:Mn=60:40), when the molar fraction of manganese in the lithium composite oxide is about 10%, the H2→H3 peak is observed at about 4.21V, and when the molar fraction of manganese increases to about 20%, the H2→H3 peak shifts toward the high voltage direction and is observed at about 4.26V.
[0136] As described above, when the cobalt content in the commercial ternary or quaternary lithium composite oxide is reduced, the content of nickel or manganese inevitably increases. In particular, when the content of manganese in the above-mentioned lithium composite oxide increases, the voltage band in which the positive electrode active material can exert an appropriate capacity becomes higher, resulting in premature degradation of the positive electrode active material that is susceptible to the high voltage operating environment. In addition, in order to reduce the risk of such a high voltage operating environment, there may be a problem of needing to change the commercial electrolyte and / or negative electrode.
[0137] However, according to an embodiment of the present invention, by providing a bimodal positive electrode active material including a nickel-based lithium composite oxide (first lithium composite oxide) and a cobalt-free lithium composite oxide (second lithium composite oxide), the voltage band in which the above-mentioned positive electrode active material can exert appropriate capacity can be shifted to a low voltage region (preferably below 4.2V).
[0138] Lithium secondary battery
[0139] According to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided. The positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, the positive electrode active material is the same as that described previously, so for convenience, its specific description is omitted, and only the remaining structures not described above are described below.
[0140] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.
[0141] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.
[0142] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.
[0143] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0144] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.
[0145] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.
[0146] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.
[0147] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.
[0148] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.
[0149] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.
[0150] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.
[0151] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0152] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.
[0153] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.
[0154] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β (0<β<2), SnO 2 , vanadium oxide, lithium vanadium oxide, a metal oxide capable of being doped and dedoped with lithium; or a composite containing the above metal compound and a carbon material such as a Si-C composite or a Sn-C composite, etc., one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbon is soft carbon (soft carbon) and hard carbon (hard carbon), and representative high-crystalline carbon is amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Me sophase pitches) and petroleum or coal tar pitch derived coke (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbon.
[0155] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.
[0156] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0157] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0158] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.
[0159] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.
[0160] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.
[0161] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0162] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.
[0163] The lithium salt may be any compound that can provide lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF 6 、LiClO 4 、LiAsF6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 , LiCl, LiI or LiB(C 2 O 4 ) 2 etc. Preferably, the concentration of the lithium salt is used in the range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and thus can show excellent electrolyte performance and enable lithium ions to move efficiently.
[0164] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.
[0165] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S can be used. Examples of the above-mentioned sulfide-based solid electrolyte material include Li 2 SP 2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are integers, Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.
[0166] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.
[0167] Examples of materials for the oxide-based solid electrolyte include Li 7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7- 3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO 4 (LISICON) etc.
[0168] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.
[0169] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0170] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).
[0171] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.
[0172] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.
[0173] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.
[0174] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.
[0175] Preparation Example 1. Preparation of positive electrode active material
[0176] Comparative Example 1
[0177] By a known co-precipitation method, Ni and Mn sulfate were prepared by using a metal salt aqueous solution of nickel sulfate and manganese sulfate mixed in a molar ratio of 75:25. 0.75 Mn 0.25 (OH) 2 Precursor (small particle precursor) and Ni with an average particle size of about 12 μm 0.75 Mn 0.25 (OH) 2 Precursor (large particle precursor).
[0178] Then, the precursor mixture in which the small particle precursor and the large particle precursor were mixed in a weight ratio of 3:7 was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and then heated in an atmosphere of O 2 The first heat treatment was carried out at 830 °C for 12 h in an O 2 The second heat treatment was carried out at 700° C. for 12 hours in a molten-liquid atmosphere to obtain the final product (bimodal type).
[0179] Comparative Example 2
[0180] By a known coprecipitation method, Ni and manganese sulfate were synthesized using a metal salt aqueous solution of nickel sulfate and manganese sulfate mixed in a molar ratio of 75:25. 0.75 Mn 0.25 (OH) 2 Precursor (small particle precursor) and Ni with an average particle size of about 12 μm 0.75 Mn0.25 (OH) 2 Precursor (large particle precursor).
[0181] Then, the precursor mixture in which the small particle precursor and the large particle precursor were mixed in a weight ratio of 7:3 was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and heated in an oven at 0 2 The first heat treatment was performed at 830° C. for 12 hours in a molten-crystal atmosphere to obtain an intermediate product.
[0182] Next, the intermediate product was mixed with Co 3 O 4 (Based on the overall composition of the final product (bimodal type), weigh so that the molar fraction of cobalt in the metal elements other than lithium is 0.02) after mixing, 2 The second heat treatment was performed in a molten-liquid atmosphere at 700° C. for 12 hours, thereby obtaining a final product (bimodal type) having a cobalt-containing coating formed thereon.
[0183] Comparative Example 3
[0184] Ni 2O3 with an average particle size of about 12 μm was synthesized by a known coprecipitation method using an aqueous solution of metal salts of nickel sulfate and manganese sulfate mixed in a molar ratio of 75:25. 0.75 Mn 0.25 (OH) 2 Precursor (large particle precursor).
[0185] Subsequently, the above-mentioned large particle precursor was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and heated in an atmosphere of O 2 The first heat treatment was carried out at 800 °C for 12 h in an O 2 The second heat treatment was carried out at 700° C. for 12 hours in a molten-liquid atmosphere to obtain a final product (large particles).
[0186] Comparative Example 4
[0187] Ni 2O3 with an average particle size of about 3 μm was synthesized by a known coprecipitation method using an aqueous solution of metal salts of nickel sulfate and manganese sulfate mixed in a molar ratio of 75:25. 0.75 Mn 0.25 (OH) 2 Precursor (small particle precursor).
[0188] Subsequently, the small particle precursor was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and heated in O 2 The first heat treatment was carried out at 800 °C for 12 h in an O 2The second heat treatment was performed at 700° C. for 12 hours in a molten-liquid atmosphere to obtain a final product (small particles).
[0189] Comparative Example 5
[0190] Ni 2O3 with an average particle size of about 3 μm was synthesized by a known coprecipitation method using an aqueous solution of metal salts of nickel sulfate and manganese sulfate mixed in a molar ratio of 75:25. 0.75 Mn 0.25 (OH) 2 Precursor (small particle precursor).
[0191] Then, the small particle precursor was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and heated in O 2 The first heat treatment was performed in a molten-liquid atmosphere at 800° C. for 12 hours to obtain an intermediate product.
[0192] Next, the intermediate product was mixed with Co 3 O 4 After mixing (weighing so that the molar fraction of cobalt in the metal elements other than lithium based on the overall composition of the final product (small particles) is 0.02), 2 The second heat treatment was performed in a molten-liquid atmosphere at 700° C. for 12 hours, thereby obtaining a final product (small particles) having a cobalt-containing coating layer formed thereon.
[0193] Example 1
[0194] Ni 2O3 with an average particle size of about 3 μm was synthesized by a known coprecipitation method using an aqueous solution of metal salts of nickel sulfate, cobalt sulfate, and manganese sulfate mixed in a molar ratio of 91:8:1. 0.91 Co 0.08 Mn 0.01 (OH) 2 Precursor (small particle precursor).
[0195] Next, the small particle precursor was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and heated in an atmosphere of O 2 The first heat treatment was performed at 800° C. for 12 hours in a vacuum atmosphere, followed by vacuum drying at 120° C. and washing with water to obtain an intermediate product.
[0196] Then, the intermediate product was reacted with Co 3 O 4 After mixing (weighing so that the molar fraction of cobalt in the metal elements other than lithium based on the overall composition of the final product (small particles) is 0.03), 2 The second heat treatment was performed at 700° C. for 12 hours in a molten-liquid atmosphere to obtain a final product (small particles).
[0197] Then, the final product (small particles) and the final product (large particles) prepared in Comparative Example 3 were mixed at a weight ratio of 1:9 to obtain a final product (double peak).
[0198] Example 2
[0199] The final product (bimodal) was prepared in the same manner as in Example 1, except that the final product (small particles) and the final product (large particles) prepared in Comparative Example 3 were mixed in a weight ratio of 2:8.
[0200] Example 3
[0201] The final product (bimodal) was prepared in the same manner as in Example 1, except that the final product (small particles) and the final product (large particles) prepared in Comparative Example 3 were mixed in a weight ratio of 3:7.
[0202] Example 4
[0203] Ni 2O3 with an average particle size of about 12 μm was synthesized by a known coprecipitation method using an aqueous solution of metal salts of nickel sulfate and manganese sulfate mixed in a molar ratio of 75:25. 0.75 Mn 0.25 (OH) 2 Precursor (large particle precursor).
[0204] Then, the large particle precursor was mixed with LiOH (Li / (metal other than Li) molar ratio = 1.05 ± 0.05) and heated in O 2 The first heat treatment was performed in a molten-crystal atmosphere at 800° C. for 12 hours to obtain an intermediate product.
[0205] Next, the intermediate product was mixed with Co 3 O 4 After mixing (weighing so that the molar fraction of cobalt in the metal elements other than lithium based on the overall composition of the final product (large particles) is 0.01), 2 The second heat treatment was performed in a molten-liquid atmosphere at 700° C. for 12 hours, thereby obtaining a final product (large particles) having a cobalt-containing coating layer formed thereon.
[0206] Then, the final product (small particles) prepared in Example 1 and the above-mentioned final product (large particles) were mixed at a weight ratio of 1:9 to obtain a final product (double peak).
[0207] The composition of the positive electrode active material (final product) prepared according to the above Preparation Example 1 was confirmed by ICP analysis and is shown in Table 1 below.
[0208] Table 1
[0209] Classification Nickel (mol%) Cobalt (mol%) Manganese (mol%) Example 1 76.3 1.1 22.6 Example 2 76.6 2.2 21.2 Example 3 77.5 3.2 19.3 Example 4 75.6 2.0 22.4 Comparative Example 1 75.5 - 24.5 Comparative Example 2 77.0 2.0 21.0 Comparative Example 3 75.0 - 25.0 Comparative Example 4 75.0 - 25.0 Comparative Example 5 73.5 2.0 24.5
[0210] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)
[0211] 94 wt % of each positive electrode active material prepared according to Preparation Example 1, 3 wt % of carbon black and 3 wt % of PVDF binder were dispersed in 30 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film having a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.
[0212] With respect to the positive electrode, a lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and LiPF was used in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7. 6 The half-cell was fabricated with the electrolyte present at a concentration of 1.15M.
[0213] Experimental Example 1. Crystal structure analysis of positive electrode active material
[0214] For the lithium secondary battery prepared in Preparation Example 2 using the positive electrode active material according to Examples 1 to 3 and Comparative Examples 1 to 3, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete two cycle formation processes at a temperature of 25°C, a voltage range of 3.0V to 4.4V, and 0.1C / 0.1C, and then charge / discharge was performed at a temperature of 25°C, a voltage range of 3.0V to 4.4V, and 0.1C / 0.1C.
[0215] At this time, the voltage (V) and battery capacity (Q) measured during initial discharge according to the above-mentioned charge / discharge conditions are present, the X-axis is the above-mentioned voltage (V), the Y-axis is the above-mentioned battery capacity (Q), and the above-mentioned battery capacity (Q) is differentiated by the above-mentioned voltage (V) to obtain a (dQ / dV) curve.
[0216] Figure 2 dQ / dV curves of lithium secondary batteries manufactured using the positive electrode active materials according to Examples 1 to 3 at the time of initial discharge are shown respectively, Figure 3 The dQ / dV curves of lithium secondary batteries manufactured using the positive electrode active materials according to Comparative Examples 1 to 3 at the time of initial discharge are respectively shown.
[0217] Reference Figure 2 and Figure 3In the case of the lithium secondary battery using the positive electrode active material according to Examples 1 to 3, there is a peak in the charging region within the voltage range of about 4.1 V to about 4.2 V, while the lithium secondary battery using the positive electrode active material according to Comparative Examples 1 to 3 does not have a corresponding peak in the voltage range below about 4.2 V.
[0218] That is, based on the above results, it can be confirmed that the lithium secondary battery using the positive electrode active material according to Comparative Examples 1 to 3 can exhibit an appropriate capacity in a voltage band of about 4.3V, while the lithium secondary battery using the positive electrode active material according to Examples 1 to 3 can exhibit an appropriate capacity in a voltage band below 4.2V.
[0219] Experimental Example 2. Evaluation of electrochemical performance of lithium secondary battery (half-cell)
[0220] The lithium secondary battery (half-cell) prepared according to Preparation Example 2 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, a voltage range of 3.0 V to 4.3 V, and a discharge rate of 0.1 C to measure the initial charge capacity, initial discharge capacity, and initial efficiency.
[0221] In addition, the same lithium secondary battery (half-cell) was charged / discharged 50 times at 25°C, a voltage range of 3.0 V to 4.3 V, and 1C / 1C using an electrochemical analyzer (Toyo, Toscat-3100), and then the ratio of the discharge capacity at the 50th cycle (cycle capacity retention) was measured.
[0222] The above measurement results are shown in Table 2 below.
[0223] Table 2
[0224]
[0225] Referring to the results in Table 2 above, the electrochemical performance of the bimodal positive electrode active material including cobalt-containing nickel-based lithium composite oxide and cobalt-free lithium composite oxide is better than the results of Comparison Examples 1 and 2 of bimodal positive electrode active materials composed only of small particles and large particles without cobalt.
[0226] In addition, referring to the results of Comparative Examples 1 and 2, even if the positive electrode active material of Comparative Example 1 is coated with cobalt to ensure that cobalt is present at an appropriate level based on the overall composition of the bimodal positive electrode active material, since the block particles themselves are cobalt-free compositions, no significant changes are confirmed by coating with cobalt.
[0227] Experimental Example 3. Analysis of Residual Lithium in Positive Electrode Active Material
[0228] The residual lithium (lithium impurities) content in the positive electrode active material prepared according to Preparation Example 1 was analyzed by pH titration. As a pH titration method, the residual lithium (lithium impurities) content was measured by pH titration of the above-mentioned positive electrode active material with an amount of 0.1M HCl used until the pH value reached 4. Specifically, 5 g of each positive electrode active material prepared according to Preparation Example 1 was added to 100 ml of deionized water (DIW), stirred for 15 minutes and filtered, 50 ml of the filtered solution was taken, and 0.1M HCl was added thereto to measure the HCl consumption according to the pH change, and LiOH and Li 2 CO 3 The sum of the contents.
[0229] The above measurement results are shown in Table 3 below.
[0230] Table 3
[0231] Classification Residual lithium content (ppm) Example 1 4472 Example 2 4216 Example 3 3966 Example 4 3422 Comparative Example 1 5478 Comparative Example 2 5050 Comparative Example 3 6968 Comparative Example 4 7616 Comparative Example 5 6263
[0232] Referring to the results of Table 3 above, it can be confirmed that, in general, the residual lithium content in the positive electrode active material according to the embodiment is lower than the residual lithium content in the positive electrode active material according to the comparative example. When the block particles are coated, the coating raw material reacts with the residual lithium present on the surface of the block particles to form a coating, resulting in a reduction in the residual lithium content. However, considering that the residual lithium content measured from the positive electrode active materials of Comparative Examples 2 and 5 according to the coating treatment with cobalt is higher than that of the embodiment, it can be confirmed that the generation of residual lithium is further suppressed in the bimodal positive electrode active material using a cobalt-containing nickel-based lithium composite oxide and a cobalt-free nickel-based lithium composite oxide.
[0233] Therefore, the residual lithium (LiOH and Li 2 CO 3 The total of the contents) can be controlled to 5,000 ppm, preferably 4,500 ppm or less.
[0234] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.
Claims
1. A positive electrode active material, which is a bimodal positive electrode active material comprising a first lithium composite oxide and a second lithium composite oxide having an average particle size larger than the average particle size of the first lithium composite oxide, wherein the positive electrode active material is characterized in that: The first lithium composite oxide includes first bulk particles containing at least nickel and cobalt. The second lithium composite oxide includes cobalt-free second bulk particles.
2. The positive electrode active material according to claim 1, characterized in that The mole fraction of nickel in the first bulk particles is greater than the mole fraction of nickel in the second bulk particles.
3. The positive electrode active material according to claim 1, characterized in that The mole fraction of manganese in the first bulk particles is smaller than the mole fraction of manganese in the second bulk particles.
4. The positive electrode active material according to claim 1, characterized in that The molar fraction of nickel in the metal elements other than lithium in the first bulk particles is greater than 0.
75.
5. The positive electrode active material according to claim 1, characterized in that The molar fraction of cobalt in the metal elements other than lithium in the first bulk particles is less than or equal to 0.
15.
6. The positive electrode active material according to claim 1, characterized in that The first blocky particle is represented by the following chemical formula 1: [Chemical formula 1] The w Nor 1-(x+y+z) Co x M1 y M2 z O2 (in, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, M1 and M2 are different from each other. 0.5≤w≤1.5,0 <x≤0.40,0≤y≤0.30,0≤z≤0.20)。 7. The positive electrode active material according to claim 1, characterized in that The second blocky particle is represented by the following chemical formula 2: [Chemical formula 2] The a Nor 1-(b+c) M3 b M4 c O 2-α X α (in, M3 is at least one selected from Mn and Al, M4 is at least one selected from Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, M3 and M4 are different elements. X is at least one anion element selected from F, P, S, Cl and Br, 0.5≤a≤1.5, 0≤b≤0.50, 0≤c≤0.20, 0≤α≤0.20).
8. The positive electrode active material according to claim 1, characterized in that The coating is present on at least a portion of the surface of the first bulk particle, The coating layer includes a metal oxide represented by the following chemical formula 3: [Chemical formula 3] Li d M5 e ON f (in, M5 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, 0≤d≤8, 0 <e≤8、0<f≤13)。 9. The positive electrode active material according to claim 8, characterized in that The coating layer present on the surface of the first massive particle comprises a cobalt-containing oxide.
10. The positive electrode active material according to claim 1, characterized in that The coating is present on at least a portion of the surface of the second bulk particle, The coating layer includes a metal oxide represented by the following chemical formula 4: [Chemical formula 4] Li g M6 h O i (in, M6 is at least one selected from Ni, Co, P, Sr, Ba, B, Ce, Cr, Mn, Mo, Na, K, Ti, Zr, Al, Hf, Ta, Mg, V, Zn, Si, Y, Sn, Ge, Nb, W, Ca, Ga, Sb, Fe, Nd and Cu, 0≤g≤8, 0 <h≤8、0<i≤13)。 11. The positive electrode active material according to claim 10, characterized in that The coating layer present on the surface of the second massive particle includes a cobalt-containing oxide.
12. The positive electrode active material according to claim 1, characterized in that The molar fraction of cobalt in the metal elements other than lithium is 0.05 or less based on the overall composition of the positive electrode active material including the first lithium composite oxide and the second lithium composite oxide.
13. The positive electrode active material according to claim 1, characterized in that The molar fraction of manganese in the metal elements other than lithium is 0.10 or more and 0.40 or less based on the overall composition of the bimodal positive electrode active material including the first lithium composite oxide and the second lithium composite oxide.
14. The positive electrode active material according to claim 1, characterized in that When a lithium secondary battery using the above positive electrode active material as a positive electrode and a lithium foil as a negative electrode is charged and discharged at 25°C, a voltage range of 3.0V to 4.4V, and a discharge rate of 0.1C, Based on the voltage V and the battery capacity Q at the time of initial discharge, the X-axis is set to the voltage V, the Y-axis is set to the battery capacity Q, and the differential value dQ / dV of the battery capacity Q to the voltage V is plotted. There is a peak in the charging region within the voltage range of 4.1V to 4.2V.
15. The positive electrode active material according to claim 1, characterized in that The coating is present on at least a portion of the surface of the second bulk particle, The coating layer includes a compound represented by LiX', wherein X' is an anion element selected from F, Cl and Br.
16. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 15.
17. A lithium secondary battery, characterized in that: The positive electrode according to claim 16 is used.